A complex relative motion between hairpin loop 2 and transmembrane domain 5 in the glutamate transporter GLT-1. (March 2015) - Rong, Xiuliang; Zhang, Xiuping; Qu, Shaogang
Abstract: Excitatory amino acid transporter 2, also known as glial glutamate transporter type 1 (GLT-1), plays an important role in maintaining suitable synaptic glutamate concentrations. Reentrant helical hairpin loop (HP) 2, as the extracellular gate, has been shown to participate in the binding of substrate and ions. Several residues in transmembrane domain (TM) 5 have been shown to be involved in the construction of the transport pathway. However, the spatial relationship between HP2 and TM5 during the recycling of glutamate has not yet been clarified. We introduced cysteine residue pairs in HP2 and TM5 of cysteine-less-GLT-1 by using site-directed mutagenesis in order to assess the proximity of HP2 and TM5. A significant decrease in substrate uptake was seen in the I283C/S443C and S287C/S443C mutants when the oxidative cross-linking agent copper(II) (1, 10-phenanthroline)3 (CuPh) was used. The inhibitory effect of CuPh on the transport activity of the S287/S443C mutant was increased after the application of glutamate or potassium. In contrast, an apparent protection of the transport activity of the I283C/S443C mutant was observed after glutamate or potassium addition. The membrane-impermeable sulfhydryl reagent (2-trimethylammonium) methanethiosulfonate (MTSET) was used to detect the aqueous permeability of each single mutant. The aqueous permeability of the I283C mutant was identical to that of the S443C mutant. The sensitivity of I283C and S443C to MTSET was attenuated by glutamate and potassium. All these data indicate that there is a complex relative motion between TM5 and HP2 during the transport cycle.